(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Thirty rats of both sexes were assigned into 5 categories of six animals apiece. Animals in the unadministered (control) group were placed on distilled water. Group 1M and Group 1F animals were administered 500 mg/kg body weight (b.w) of T. conophorum aqueous nut extract whereas animals in Group 2M and Group 2F were administered 750 mg/kg dosage of the extricate (0.5 ml) orally once daily for 32 days. Phytoconstituents present in the extract include: saponins, flavonoids, tannins, phenols and alkaloids. The extract at 750mg/kg b.w notably (p<0.05) raised extracellular glucose in masculine rats when matched with males that received 500 mg/kg b.w. The 500 mg/kg dose of the extract appreciably (p<0.05) elevated BUN in both sexes, but with reduction in both groups at 750 mg/kg b.w when juxtaposed with their respective untreated animals. The extract at 500 mg/kg b.w increased LDH activity in male group when compared with male rats that received 750 mg/kg dose. The 750-extract dosage did not statistically (p>0.05) alter LDH activity in both sexes. The extract at 500 and 750mg/kg b.w increased the 3rd‒6th swim in male rats. Substantive (p<0.05) rise in swimming endurance time was first noticed at the 2nd swim when matched up with the control and group treated 500 mg/kg b.w, in female rats. Sequel to these research findings, it is hypothesized that the anti-weakness effect of T. conophorum might be adduced to delayed increase in lactate and reduction in protein catabolism